A comparative study on the mechanical properties of clay-modified epoxy adhesive by using different clay types - Surip, Siti Norasmah; Ismail, A. H.; Anuar, Hazleen (2010)
A comparative study on the mechanical properties of clay-modified epoxy adhesive by using different clay types was ascertained. The effects on different clay types which are micron-sized clay and nano-sized clay that modified the epoxy adhesive were determined. The clay (5 wt. %) along with hardener (10%) was dispersed in the epoxy adhesive (90%) in order to investigate the mechanical properties of epoxy adhesive after added the clay. The adherend used for shear and tensile test are wood. The optimum loading was determined to investigate the differences between neat epoxy adhesive with epoxy adhesive added with clay. The results shows that the tensile strength was increase by using micron clay while shear and impact strength was increase by using nano clay. The function of clay to enhance the properties of epoxy adhesive is more effective when the clay is well dispersed in the epoxy adhesive. FESEM shows that the nano clay was well dispersed in the epoxy adhesive while micron-sized sized clay was partially intercalated.